Reconstruction of Moderate Religious Strengthening in Malay Society - Rohim, Abdul; Holijah, Holijah; Jamil, Syahril; Rizal, M.; Rudi, Yudi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study examines the reconstruction of religious moderation within the Malay community of Muntok City, Bangka Belitung, amid contemporary socio-religious challenges. Although historically recognized for its strong interreligious harmony grounded in Malay local wisdom, recent social changes, transnational religious influences, and digital media exposure have begun to reshape patterns of religious interaction. This research addresses two key questions: how the reconstruction of religious moderation is carried out and what factors influence its strengthening in the local context. Employing a qualitative case study approach, primary and secondary data were collected through in-depth interviews with religious leaders, Malay traditional leaders, government representatives, and community members, supported by participant observation and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that religious moderation in Muntok is reconstructed through the revitalization of core Malay values, musyawarah (deliberation), mutual cooperation, kinship solidarity, and cultural politeness, integrated with moderate Islamic principles. Religious and customary leaders function as moral authorities and conflict mediators, while educational institutions, social networks, government policies, and digital literacy initiatives provide structural support. The study concludes that religious moderation in Muntok is not a newly constructed paradigm but a contextual reinforcement of historically embedded cultural-religious values. Sustainable strengthening requires systematic educational programs, cross-faith dialogue, and proactive digital engagement to ensure resilience against exclusivist ideologies in the digital era.